Optimization of Mixed Bacillus Cultures as An Inoculant in Northern Thai Style Fermented Soybeans (Thua-nao) by Mixture Design - Patcharin Phokasem (Science Faculty of Chiang Mai University, 2019)
We aim to investigate the influence of formulation of mixed culture ratios in laboratory scale fermentations of Northern Thai-style fermented soybeans; Thua-nao using a mixture design approach. An optimized mixture design was used to evaluate the effects of mixed culture ratios (Bacillus subtilis MCG8, B39, KMB2 and B. amyloliquefaciens MHS1) on the five responses (soluble proteins, vitamin B12 contents, diameter of inhibition zone against Staphylococcus aureus, viable counts and pH). The experimental results showed that the mixed culture ratios significantly affected the inhibitory ability against S. aureus, vitamin B12 content and final pH of the products. The two best cultures ratios were optimized for the maximal predicted diameter of the S. aureus inhibition zone (17.08 mm) (consisting of B. subtilis MCG8 (13%), KMB2 (73%) and B. amyloliquefaciens MHS1 (14%)) and optimized vitamin B12 content (3.26 ng/g wet weight) (consisting of B. subtilis KMB2 (42%) and B. amyloliquefaciens MHS1 (58%)). The properly mixed culture ratios obtained from this study could provide an improved added value for antibacterial activity against S. aureus and optimized vitamin B12 levels in fermented soybean products. The optimum mixed cultures ratios could enhance the nutritious values of fermented soybeans. We also analyzed the levels of gamma-polyglutamic acid (g-PGA) that were produced by the selected cultures. This study showed that the statistical mixture design is a useful tool to create properly mixed culture ratios for use in fermented foods.